IDENTIFIKASI KERENTANAN DAN SEBARAN LONGSOR LAHAN SEBAGAI UPAYA MITIGASI BENCANA DI KECAMATAN BENER KABUPATEN PURWOREJO - Nursa’ban, Muhammad (Universitas Pendidikan Indonesia, 2010)
The objectives of this research are to: Investigating the level of landslide susceptibility and identifying the distribution of landslide susceptibility locations in Bener district Purworejo regency. Land units were chosen as the sample using the purposive area sampling technique. Eleven land units were obtained by overlay maps of slope, geology, and soil types. Data collecting was conducted with observation method and documentation to be analyzed by qualitative deskriptif. Findings shown that (1) the level of landslide susceptibility that is in four categories are low, medium, high, and very high. The distributions of low landslide susceptibility covered about 24042750,21 m2 (3 land units). The medium categories covered about 67768254,22 m2 (4 land units). High categories covered about 4125389,95 m2 (2 land units). The very high categories covered about 6256242,28 Â m2 (2 land units)